Association between pro-inflammatory diet and fecal incontinence: a large population-based study - Wang, Haiyang; Liu, Zihan; Lu, Xingfu; Luan, Enyu; Dong, Tingting; Li, Can; Lv, Yanni; Wu, Erkang; Shen, Tao (Frontiers in Nutrition, 2025)
BackgroundIt is widely acknowledged that dietary habits play a pivotal role in maintaining optimal intestinal health. Fecal incontinence (FI) is a distressing and often stigmatized inflammatory ailment with a strong correlation to a multitude of intestinal disorders. However, the associations between diets and FI are largely unknown.MethodsIn this study, we collected cross-sectional data from 31,034 participants enrolled in the National Health and Nutrition Examination Survey (NHANES). To investigate the relationship between pro-inflammation diet and the prevalence of FI, dietary inflammatory index (DII) was calculated, and participants were categorized into three tertiles. Meanwhile, we identified key dietary factors for FI using multiple machine learning algorithms. Finally, we assessed the mediation role of inflammatory indicators on the association of key dietary factors with FI through mediation analysis.ResultsAfter adjustment for potential confounding variables, our results showed the highest tertile exhibited dramatically increasing prevalence of FI compared to the lower tertile (OR 1.27, 95% CI 1.06–1.53), suggesting a positive association between DII and FI. We also identified total saturated fat, polyunsaturated fatty acid, vitamin A, β carotene, vitamin B2, and iron are the primary dietary factors associated with FI. Based on these dietary factors, we developed a novel FI risk prediction model. The receiver operating characteristic (ROC) analyses conducted on both the training and independent validation cohorts demonstrate favorable predictive performance for FI in nearly 10,000 participants. Moreover, our findings indicate that consumption of these key dietary factors can trigger an intestinal inflammatory response by mediating neutrophils and lymphocytes, which in turn contributes to the development of FI.ConclusionIn conclusion, this study not only elucidates the fundamental roles of pro-inflammatory diet in inducing intestinal inflammation and eventually in resulting FI, but also provides a FI risk prediction tool based on dietary factors, which may prove beneficial in the clinical diagnosis of FI.